Growth performance of Spirulina under immobilised and suspended cultivation - Phan, Nhat-Truong; Tran-Thi, Tuong-Vy; Vo-Thi, Le-Dieu; Vo-Van, Minh; Trinh-Dang, Mau (Hue University Journal of Science: Natural Science, 2025)
Immobilised cultivation is a water- and harvest-efficient alternative to suspended growth for Spirulina (Arthrospira platensis), but side-by-side tests under controlled nutrients are scarce. In this study, we compared 6-day growth on agar plates versus suspension across Zarrouk 0.5×, 1×, and 2× in two semi-continuous cycles, measuring biomass, instantaneous specific growth rate, and plate coverage. In Cycle 1, immobilised cultures significantly outperformed suspension at 1× and 2× (µ = 0.312 vs. 0.263 day⁻¹ and 0.328 vs. 0.254 day⁻¹), with no difference at 0.5×. After harvest and medium reuse (Cycle 2), the mean growth rate decreased by ~30–54% in all treatments; however, the immobilised culture remained superior at 2× (0.232 vs. 0.181 day⁻¹). Kinetically, the suspension showed a first-day peak in the specific growth rate (≈0.55–0.75 day⁻¹), followed by monotonic decay and early plateaus. In contrast, the immobilised culture maintained a steadier growth rate and continued to increase at 1×–2×. Plate coverage increased from ~20–23% to 55–74% by day 6 in Cycle 1, and to 53–67% in Cycle 2. Late-stage yellowing at treatments with ≤1× Zarrouk in Cycle 2 signaled nutrient depletion. These findings suggest that immobilised cultivation may be advantageous for high-density Spirulina production systems, supporting more sustainable and resource-efficient microalgae bioprocesses.